Rating authors' contributions to collaborative research: the PICNIC survey of university departments of pediatrics. Pediatric Investigators' Collaborative Network on Infections in Canada. - Davies, H D (1996)
OBJECTIVES: To determine how department chairs in pediatrics rate involvement in medical research and to determine whether faculty deans' offices have written criteria for evaluating research activity when assessing candidates for promotion or tenure. DESIGN: Cross-sectional mailed survey and telephone survey. SETTING: Canadian faculties of medicine. PARTICIPANTS: Chairs of the 16 Canadian university departments of pediatrics and deans' offices of the 16 university medical faculties. MAIN OUTCOME MEASURE: Weight assigned by department chairs to contributions to published research according to author's research role and position in list of authors and the method of listing authors. RESULTS: Fifteen of 16 chairs responded. Twelve submitted a completed survey, two described their institutions' policies and one responded that the institution had no policy. Eleven reported that faculty members were permitted or requested to indicate research roles on curricula vitae. There was a consensus that all or principal investigators should be listed as authors and that citing the research group as collective author was insufficient. The contribution of first authors was rated highest for articles in which all or principal investigators were listed. The contribution of joint-principal investigators listed as first author was also given a high rating. In the case of collective authorship, the greatest contribution was credited to the principal investigator of the group. Participation of primary investigators in multicentre research was rated as having higher value than participation in single-centre research by seven respondents and as having equal value by four. Only one dean's office had explicit written criteria for evaluating authorship. CONCLUSIONS: Most departments of pediatrics and medical faculty dean's offices in Canadian universities have no criteria for assessing the type of contribution made to published research. In view of the trend to use multicentre settings for clinical trials, guidelines for weighting investigators' contributions are needed.